A rapid in vivo screen for pancreatic ductal adenocarcinoma therapeutics - Ozhan Ocal; Victor Pashkov; Rahul K. Kollipara; Yalda Zolghadri; Victoria H. Cruz; Michael A. Hale; Blake R. Heath; Alex B. Artyukhin; Alana L. Christie; Pantelis Tsoulfas; James B. Lorens; Galvin H. Swift; et al. (The Company of Biologists, 2015)
Pancreatic ductal adenocarcinoma (PDA) is the fourth leading cause of cancer-related deaths in the United States, and is projected to be second by 2025. It has the worst survival rate among all major cancers. Two pressing needs for extending life expectancy of affected individuals are the development of new approaches to identify improved therapeutics, addressed herein, and the identification of early markers. PDA advances through a complex series of intercellular and physiological interactions that drive cancer progression in response to organ stress, organ failure, malnutrition, and infiltrating immune and stromal cells. Candidate drugs identified in organ culture or cell-based screens must be validated in preclinical models such as KIC (p48Cre;LSL-KrasG12D;Cdkn2af/f) mice, a genetically engineered model of PDA in which large aggressive tumors develop by 4 weeks of age. We report a rapid, systematic and robust in vivo screen for effective drug combinations to treat Kras-dependent PDA. Kras mutations occur early in tumor progression in over 90% of human PDA cases. Protein kinase and G-protein coupled receptor (GPCR) signaling activates Kras. Regulators of G-protein signaling (RGS) proteins are coincidence detectors that can be induced by multiple inputs to feedback-regulate GPCR signaling. We crossed Rgs16::GFP bacterial artificial chromosome (BAC) transgenic mice with KIC mice and show that the Rgs16::GFP transgene is a KrasG12D-dependent marker of all stages of PDA, and increases proportionally to tumor burden in KIC mice. RNA sequencing (RNA-Seq) analysis of cultured primary PDA cells reveals characteristics of embryonic progenitors of pancreatic ducts and endocrine cells, and extraordinarily high expression of the receptor tyrosine kinase Axl, an emerging cancer drug target. In proof-of-principle drug screens, we find that weanling KIC mice with PDA treated for 2 weeks with gemcitabine (with or without Abraxane) plus inhibitors of Axl signaling (warfarin and BGB324) have fewer tumor initiation sites and reduced tumor size compared with the standard-of-care treatment. Rgs16::GFP is therefore an in vivo reporter of PDA progression and sensitivity to new chemotherapeutic drug regimens such as Axl-targeted agents. This screening strategy can potentially be applied to identify improved therapeutics for other cancers.